2014
DOI: 10.1021/ja5044374
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nuclear Polarization of 1H, 13C, and 59Co in a Tris(ethylenediamine)cobalt(III) Crystalline Lattice Doped with Cr(III)

Abstract: The study of inorganic crystalline materials by solid-state NMR spectroscopy is often complicated by the low sensitivity of heavy nuclei. However, these materials often contain or can be prepared with paramagnetic dopants without significantly affecting the structure of the crystalline host. Dynamic nuclear polarization (DNP) is generally capable of enhancing NMR signals by transferring the magnetization of unpaired electrons to the nuclei. Therefore, the NMR sensitivity in these paramagnetically doped crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 130 publications
2
58
0
2
Order By: Relevance
“…DNP MAS NMR was also implemented for 1D and 2D 13 C and 29 Si measurements in unlabeled samples, relieving the need for elaborate and tedious sample labeling [40][41][42][43][44][45] . However, rapid deployment of the technique for extensive structural 2 characterization in biological systems is still hampered by low-resolution spectra [46][47] with some exceptions reported [48][49][50] .…”
Section: Introductionmentioning
confidence: 99%
“…DNP MAS NMR was also implemented for 1D and 2D 13 C and 29 Si measurements in unlabeled samples, relieving the need for elaborate and tedious sample labeling [40][41][42][43][44][45] . However, rapid deployment of the technique for extensive structural 2 characterization in biological systems is still hampered by low-resolution spectra [46][47] with some exceptions reported [48][49][50] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was shown that paramagnetic metal ion chelates can be used as polarizing agents for DNP in biomolecules and molecular crystals . Similarly, in the early days of DNP, paramagnetic defect sites were used to polarize single crystals at low magnetic fields and extremely low temperatures ,.…”
Section: Figurementioning
confidence: 99%
“…[9] Recently it was shown that paramagnetic metal ion chelates can be used as polarizing agents [10] for DNP in biomolecules [11] and molecular crystals. [12] Similarly, in the early days of DNP, paramagnetic defect sites were used to polarize single crystals at low magnetic fields and extremely low temperatures. [13,14] Here we expand this approach and show that paramagnetic metal ions incorporated as dopants can be used efficiently for sensitivity enhancement in powders of micron sized inorganic solids.…”
mentioning
confidence: 99%
“…Among those, dynamic nuclear polarization (DNP), which uses microwave irradiation of EPR transitions to drive the magnetization from unpaired electrons to the nuclear spins, [86,87] provides dramatic enhancements, expanding the applicability of NMR to more and more complex chemical entities. [88][89][90] After the pioneering studies by Griffin and co-workers on lyophilized samples, [91][92][93] and Cross and Opella on oriented samples, [94] also the solid-state NMR characterization of biological macromolecules has flourished significantly, because of improved hardware, pulse sequences and sample preparation approaches. [85] Higher magnetic fields have led to improved sensitivity and resolution, especially when coupled to fast magic angle spinning.…”
Section: Biomaterials From the Nmr Standpointmentioning
confidence: 99%